Notch1 hallmarks fibrillary depositions in sporadic Alzheimer’s disease - Brai, Emanuele; Alina Raio, Noemi; Alberi, Lavinia (Acta Neuropathologica Communications, 2016)
Notch1 signaling is a cellular cascade with a fundamental role from brain development to adult brain function. Reduction in Notch1 affects synaptic plasticity, memory and olfaction. On the other hand, Notch1 overactivation after brain injury is detrimental for neuronal survival. Some familial Alzheimer’s disease (FAD) mutations in Presenilins can affect Notch1 processing/activation. Others report that Notch1 is overexpressed in sporadic Alzheimer’s disease (AD). These works indicate that imbalances in Notch1 may be implicated in AD pathophysiology. In this study, we addressed whether Notch1 alteration can be considered a hallmark of AD.